The purification of AISI 420 stainless steel in laser solid forming. (5th January 2016) - Song, Menghua; Lin, Xin; Liu, Fenggang; Yang, Haiou; Huang, Weidong
Abstract: A series of AISI 420 stainless steel deposits were prepared by laser solid forming under different oxygen partial pressures. The variation of the oxygen concentration of the deposit with the oxygen partial pressure was investigated. It is found that the purification occurs when the oxygen partial pressure is lower than a certain threshold. By considering the transfer of gaseous oxides in gas phases, a novel mechanism was developed to explain the purification. The predicted oxygen adsorption/desorption behavior shows a reasonable consistent with the experiment result. It is indicated that volatile oxides play a significant role in the purification. The decrease of the oxygen partial pressure and increase of the contents of elements forming volatile oxides and the original oxygen in the deposited material all promote the purification. Graphical abstract: Highlights: The purification of AISI 420 stainless steel was found in laser solid forming. Recycled powder with excess oxygen can be used to deposit qualified components. Oxygen adsorption/desorption mainly takes place in the molten pool stage. A novel mechanism of considering the effect of gaseous oxides was developed. Volatile oxides play a significant role in the purification.